Pendampingan Gerakan Literasi Dengan Metode ABCD Pada Satuan Pendidikan Anak Usia Dini - Masturoh, Umi; Arif, Muhamad (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
This Community Service Program (PKM) aims to improve literacy movements in Early Childhood Education (PAUD) units using the Asset-Based Community Development (ABCD) approach. Low literacy skills in early childhood are often caused by limited resources, skills, and understanding of teachers and parents regarding the importance of early literacy. Through the ABCD method, this activity identifies the potential and assets owned by the PAUD community, including teachers, parents, and the surrounding environment, to jointly develop effective and sustainable literacy programs. This mentoring activity includes training for teachers and parents in developing interesting literacy activities, creating reading corners in the PAUD environment, and mentoring in implementing literacy activities based on games and exploration. This method focuses on empowering local assets and the active participation of all members of the PAUD community, so as to build collective awareness regarding the importance of early literacy. The results of the activity show an increase in children's interest in reading and teachers' skills in implementing literacy activities in PAUD. It is hoped that this program can be a model for a broader literacy movement in the context of early childhood education.